2015
DOI: 10.1088/1751-8113/48/18/185303
|View full text |Cite
|
Sign up to set email alerts
|

Role of complementary correlations in the evolution of classical and quantum correlations under Markovian decoherence

Abstract: Quantum correlation lies at the very heart of almost all the non-classical phenomena exhibited by quantum systems composed of more than one subsystem. In the recent days it has been pointed out that there exists quantum correlation, namely discord which is more general than entanglement. Some authors have investigated that for certain initial states the quantum correlations as well as classical correlation exhibit sudden change under simple Markovian noise. We show that, this dynamical behavior of the both typ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…Hence, the freezing of coherence might provide a deeper insight into the peculiar phenomenon of frozen quantum correlations under local flip channels (see also Ref. [67]), as the latter just reduce to coherence for t ≤ t ⋆ under the conditions we identified.…”
Section: 210401 (2015) P H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 73%
“…Hence, the freezing of coherence might provide a deeper insight into the peculiar phenomenon of frozen quantum correlations under local flip channels (see also Ref. [67]), as the latter just reduce to coherence for t ≤ t ⋆ under the conditions we identified.…”
Section: 210401 (2015) P H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 73%
“…Considering two complementary observables acting on each one of the subsystems of a bipartite system, it was shown that the sum of the local correlations between such observables is a good measure of the quantum correlations shared by the composite system. The general conclusion is that the mixedness of the initial bipartite state is not enough for the SCP, but the state also needs to present certain asymmetry with respect to local complementary observables [145]. Moreover, they also proved that a pure state will never present the SCP and that the freezing phenomena is not a general property of all the Bell-diagonal states.…”
Section: A Markovian Dynamics Of Correlationsmentioning
confidence: 96%
“…A new interpretation of the SCP was introduced employing the idea of complementary correlations [145]. Considering two complementary observables acting on each one of the subsystems of a bipartite system, it was shown that the sum of the local correlations between such observables is a good measure of the quantum correlations shared by the composite system.…”
Section: A Markovian Dynamics Of Correlationsmentioning
confidence: 99%
“…Although E t,0 and E tp,0 should be completely positive by construction, the map E t,tp need not be completely positive and not even positive because the inverse E −1 tp of a completely positive map E tp need not be positive. Composition (18), originating from the existence of the inverse for all positive times, allows us to introduce the notion of divisibility. The family of dynamical maps is said to be P-divisible when propagator E t,tp is positive as well as trace-preserving, and CP-divisible if E t,tp is CPTP for all 0 < t p < t [14].…”
Section: Non-markovianity Measuresmentioning
confidence: 99%
“…[17], considering the case of Bell-diagonal states under the action of non-dissipative environments, the authors proved that all bona fide measures of quantum correlations virtually present the freezing effect under the same dynamical conditions. Besides, using the quantum discord as a measure for quantum correlations, the authors of [18] proved that a pure state never present the SCP and that the freezing phenomena is not a general property of all the Bell-diagonal states.…”
Section: Introductionmentioning
confidence: 99%